Aung San Suu Kyi : fearless voice of Burma - Stewart, Whitney, 1959- (Minneapolis : Lerner Publications, 1997)
A biography of the Burmese leader who won the Nobel Peace Prize in 1991 while under house arrest
Includes bibliographical references (p. 125) and index
Keywords: Aung San Suu Kyi -- Juvenile literature; Aung San Suu Kyi, -- 1945-; Democracy -- Burma -- Juvenile literature; Politicians -- Burma -- Biography -- Juvenile literature; Politicians; Women -- Biography; Burma -- Politics and government -- 1988- -- Juvenile literature; Burma -- Politics and government -- 1948- -- Juvenile literature; Burma -- Politics and government -- 1948-; Burma -- Politics and government -- 1988-